Porphyromonas gingivalis lipopolysaccharide affects the angiogenic function of endothelial progenitor cells via Akt/FoxO1 signaling. (13th June 2022) - Deng, Hui; Gong, Yixuan; Chen, Yuan; Zhang, Guigui; Chen, Hui; Cheng, Tianfan; Jin, Lijian; Wang, Yi
Abstract: Aims: Endothelial progenitor cells (EPCs) function as the angiogenic switch of many physiological and pathological conditions. We aimed to investigate the effects of Porphyromonas gingivalis lipopolysaccharide on the angiogenic capacity of EPCs and delineate the underlying mechanisms. Materials and Methods: EPCs were isolated from human umbilical blood. CCK‐8 assay was undertaken to analyze the cell viability. The migration and tube formation capacity were assessed by wound healing and tube formation, respectively. The protein expression of Akt/p‐Akt, endothelial nitric oxide synthase (eNOS)/p‐eNOS, and Forkhead box O1 (FoxO1)/p‐FoxO1 was determined by Western blot. The intracellular localization of FoxO1 was evaluated by immunofluorescent staining. Results: P. gingivalis LPS at 10 μg/ml significantly increased the viability (10.9 ± 2.9%), migration (16.3 ± 3.1%), and tube formation (38.6 ± 5.5%) of EPCs, along with increased phosphorylation of Akt, eNOS, and FoxO1. Mechanistically, Akt inhibition by specific inhibitor wortmannin and FoxO1 forced expression by adenovirus transfection in EPCs markedly attenuated the P. gingivalis LPS‐induced eNOS activation, tube formation, and migration. Moreover, P. gingivalis LPS‐induced phosphorylation and nuclear exclusion of FoxO1 were blunted by Akt inhibition. Conclusions: The present study suggests that P. gingivalis LPS could affect the angiogenic function of EPCs through the Akt/FoxO1 signaling. The current findings may shed light on the clinical association of periodontitis with aberrant angiogenesis seen in atherosclerotic plaque rupture.